The Influence of SQ3R Technique and Students’ Reading Interest towards Students’ Reading Comprehension Achievement - Amiruddin, Amiruddin (Yayasan Sembilan Pemuda Indonesia, 2022)
This study was experimental research. The writer conducted this study at senior high school of SMK Negeri 3 Palembang. This study investigated to find out whether or not : (1) there is significant difference in reading comprehension achievement between the students who both have high reading interest taught by using SQ3R technique and those who are taught by using conventional technique, (2) there is significant difference in reading comprehension achievement between the students who both have low reading interest taught by using SQ3R technique and those who are taught by using conventional technique, (3) there is significant difference in reading comprehension achievement between the students who have high reading interest and low reading interest taught by using SQ3R technique, (4) there is significant difference in reading comprehension achievement between students who have high reading interest and low reading interest taught by using conventional strategy, (5) there is significant interaction effect of SQ3R strategy and reading interest towards the students’ reading comprehension achievement. From the finding it was found that SQ3R contributed to improve students reading comprehension achievement.